2016
DOI: 10.11604/pamj.2016.24.158.7795
|View full text |Cite
|
Sign up to set email alerts
|

Early growth in preterm infants after hospital discharge in rural Kenya: longitudinal study

Abstract: IntroductionPrematurity is the single most important cause of mortality during the neonatal period. The early growth of these infants has been shown to be a predictor of their later growth and neurodevelopmental outcomes. The objective of this study was to establish the determinants of early growth in preterm infants after hospital discharge at the Kitui District Hospital, Kenya.MethodsA short longitudinal study design was adopted to execute the study. During the period of April and June 2014, all the preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 5 publications
3
8
1
5
Order By: Relevance
“…Several studies have reported similar ndings of high proportion in poor weight gain among preterm (3,12,15,16), contrarily other studies have found marked advancement in the growth of the preterm (17,18). The difference observed across these studies in comparison to this study could be explained by the differences in characteristics of study participants, the different existing feeding protocols and the support available for supervising feeding of these vulnerable neonates.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Several studies have reported similar ndings of high proportion in poor weight gain among preterm (3,12,15,16), contrarily other studies have found marked advancement in the growth of the preterm (17,18). The difference observed across these studies in comparison to this study could be explained by the differences in characteristics of study participants, the different existing feeding protocols and the support available for supervising feeding of these vulnerable neonates.…”
Section: Discussionsupporting
confidence: 50%
“…Correspondingly, these studies (3,12) reported the association of low maternal education and poor weight gain among preterm. Education always empowers mothers in all aspects and should therefore be emphasized across countries at large.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Only in the last consultations, the male gender was predominant, but in relation to the weight gain, the female gender found statistical significance. Studies that indicate the profile of the attendees also vary in the predominance of males 17 or females 10 , 20 - 21 , and other studies related to growth also show that girls are the ones that gain less weight during outpatient follow-up 21 - 22 .…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the data on GA and birth weight present in Table 1, this study found that the lower the gestational age and the birth weight, the more frequent and the greater the follow-up visits are. Some researches show this need for more frequent follow-up when they affirm that low birth weight and prematurity are related to an increase in morbidity and mortality, chronic conditions and readmissions 2 - 3 , 9 , 19 , 27 - 31 , as well as to the greater risk of growth deficit 3 , 21 , developmental delays and cognitive and behavioral problems 3 , 7 , 31 - 32 . In addition, growth must be closely monitored in the first year of life of patients with this profile, thus ensuring optimal brain nutrition and reducing risks of neurodevelopmental delays 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%